Adoption of an Electronic Template to Promote Evidence-Based Practice for Policies, Procedures, Guidelines, and Directives Documents. Issue 4 (July 2018) - Corey, Juliann; O'Donoghue, Sharon C.; Kelly, Veronica; Mackinson, Lynn; Williams, Donna; O'Reilly, Kristin; DeSanto-Madeya, Susan
Abstract : Background: Policies, procedures, and guidelines standardize care, meet regulatory requirements, and can promote safety in clinical practice. The existing protocols, policies, guidelines, and directives (PPGDs) at a level 1 trauma academic medical center were underused by the intensive care unit clinicians and did not always clearly represent the supporting evidence. Aims: The goals of this project were to update the Critical Care Practice Manual (CCPM) and to ensure that clinical practice was aligned with best evidence. The aim was to design a new PPGD template that used technology to enhance the presentation and functionality of these documents. Methods: Nurse project consultants reviewed every PPGD and solicited feedback from critical care nurses who consistently identified 2 barriers to utilization of CCPM: difficulty finding PPGDs and the cumbersomeness of lengthy policies. This improvement project used the principles of the Plan-Do-Study-Act cycle to test changes in real time. When 95% of the PPGDs were in the new format, a 22-question survey was created to elicit feedback from the direct care nurses who used the PPGD in the new electronic format. Results: On the basis of the survey results, nurses at the medical center accessed a PPGD at least once a month. The overall results indicated that the respondents agreed or strongly agreed that the PPGDs provided guidance (85%), reflected current practice (76%), were clear and concise (75%), and were evidence based (73%). Only 24% of those surveyed were still having difficulty finding PPGDs. Discussion/Conclusion: To facilitate timely modification and early adoption of the new PPGD format, the Plan-Do-Study-Act cycle was effectively used. The CCPM adopted a new electronic format that met the aims of the project. When making a commitment to develop evidence-based practice policies and guidelines, it is important to revisit the process, consider ongoing support, and educate frontline staff as applicable. The new template restored and enhanced the standardization of PPGDs. Technology can enhance usability and improve functionality, but it can also prove to be frustrating when implementing changes that use it, especially if users are not comfortable with it.